Pengaruh Harga Dan Promosi Online Terhadap Keputusan Pembelian Buket Pada Usaha Omah Bouquet Bendogerit Kota Blitar - Desi Fitri Nur Hasanah; Hanik Amaria (International Forum of Researchers and Lecturers, 2024)
Micro, Small and Medium Enterprises (MSMEs) are companies that produce goods to meet the needs of local communities. To attract customers in the face of stiff competition, business owners must plan their prices and internet marketing tactics. The aim of this research is to find out whether discounts and internet sales influence customers' decisions to buy products at the Omah Bouquet Bendogerit shop, Blitar City. Omah Bouquet company customers who have made purchases are the subjects of this research, and questionnaires are used as a data collection tool. Respondents in this study totaled 124 people. A quantitative approach is the research method used. This research uses multiple linear regression analysis as the analysis method. At a significance level of 0.000<0.05, research findings show that “the price variable (X1) has a significant and positive effect on the purchasing choice variable (Y). At a significance level of 0.000<0.05, the online promotion variable (X2) has a significant and positive effect on the purchasing choice variable (Y). At the significance threshold of 0.000 < α 0.05, the price variables (X1) and online promotions (X2) jointly influence purchasing choices (Y).”